Controle da alimentação, controle da vida: controvérsias midiático-discursivas e biopolíticas e biossociabilidades do consumo alimentar - Teixeira, Lucas de Vasconcelos (2022)
The theme of this research focuses on food consumption as a stage where the effects of the composition and recomposition of subjectivation processes are visible, where subjects are governed or begin to regulate their own actions based on agency or power organizations. Today, a clash is taking place about the hegemony over Brazilian food consumption, and since the dominant power-knowledge is not stabilized, this is a propitious moment to analyze the manifestation of these agencies in communication processes in the social fabric under tension. By aligning communication, consumption and food, this research aims to define the problem of the biopolitical and biosociability intersections regarding what is meant by healthy eating and its modalizing discourses, in addition to the modes of material and symbolic dominance that arise from the consumption of foods and drinks and their spill over effect on other social fields. The object concerns the clashes that make the controversy visible regarding natural versus ultra-processed foods in media-discursive communications as the actors of this controversy seek to legitimize their own concept of healthy eating, conforming certain biopolitical priorities in these consumption relations. As such, the research problem of the thesis is: how and to what extent do the media-discursive controversies of Brazilian food consumption enable the biopolitics and biosociabilities in the subjectivation process of the subjects. The theoretical framework is built on studies on mediatization, communication, consumption, actor-network theory, biopolitics/biosociability and forms of power, in addition to the production of meanings attributed to food. The methodology contemplates a triangulation of methods: content analysis, cartography of controversies (CC) and a Foucaultian discourse analysis. The empirical research involves two material collection stages, interviews with representatives of eight class entities, academia and civil society, and, on the other hand, a mapping of the fanpages of two of these entities, in addition to one industry and one kitchen chef / digital influencer, all related to the controversy of natural versus ultra-processed foods, in order to form a corpus with both primary and secondary data. Among the results, we highlight that the use of scientific data was the common thread of the discursive singularization relations game on both sides of the controversy, penetrating their statements and the six discursive formations identified. Throughout this study, we were able to observe the power relations in action for the production and circulation of meanings and truths in an amalgam of the visible with the enunciable, in addition to the ascending character of power, that is, of the micro to the macropower of the social fabric. We also emphasize the privatization of dietary behavior and practices defended by the food industries and related entities, on one hand, and a stronger focus on the collective and the improvement of population health promoted by entities favorable to natural food, on the other. We emphasize, however, that both sides of the controversy make use of discursive rarefactions in an attempt to dominate the random event of the discourse. The problem definition and the results of this work have academic and social implications, such as the detection of engendered knowledge and powers in the food consumption rationale of Brazilians, with various communicational ideas on how to eat and what is healthy food, among other biopolitical and biosociability modalities. We can also mention the mediatization of what is eaten and drunk, with the mediatized production of meanings about consumption putting versions of the truth into circulation materialized as discourse, which are visible in everyday consumption practices.